Three-dimensional Printing, Bioink, Organ Printing, and Tissue Engineering Technologies, and Their Application in Modern Anatomical Pedagogy - Gyanraj Singh; Malay Mohapatra (Wolters Kluwer Medknow Publications, 2023)
In the evolving landscape of anatomy education, this review highlights the game changing advancements and their educational implications, focusing on the integration of three-dimensional (3D) printing, bioinks, organ printing, and tissue engineering technologies. While traditional teaching methodologies offer basic foundational knowledge, there are recognized gaps, particularly in providing a dynamic understanding of the human anatomy. 3D printing technologies, including digital anatomical printing and polyjet, emerge as crucial tools for bridging this gap and allowing the creation of customized and detailed anatomical models that facilitate a deeper understanding of the subject. Bioinks play a vital role in developing interactive tissue models, enhancing students' engagement with living tissues and providing insight into cellular functions and physiological processes. The review also explores organ printing and contribution of tissue engineering in offering detailed organ replicas and biological substitutes enhancing students' interaction and understanding of anatomy further. These innovations significantly influence modern anatomical pedagogy by fostering interactive learning, providing personalized educational tools and preparing students effectively for their future careers in healthcare. This comprehensive review aims not only to explore these technologies but also to anticipate the future of anatomical education, offering a vision where learning is as intricate and dynamic as the anatomy it elucidates.